2020
DOI: 10.1016/j.eats.2019.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Different Techniques for the Management of Meniscal Ramp Lesions Using Standard Anterior Portals

Abstract: There is strong association between meniscal lesions and anterior cruciate ligament injuries. Recently, light was shown on a new entity: ramp lesions. The incidence of these lesions and their management is still unclear. Although some believe that some lesions, when stable, can be managed conservatively, most surgeons repair ramp tears. Accessibility of these tears is challenging; they are best accessed through posterior portals, which is time-consuming and poses potential risk to vital structures. Our techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 16 publications
(19 reference statements)
0
15
0
Order By: Relevance
“…4,9,15 However, to our knowledge, no techniques have been reported that enable full visualization of the ramp lesion directly from the anterior compartment using an arthroscope placed through the anterolateral portal (without posteromedial visualization through the intercondylar notch) and repair of the lesion from the anteromedial portal using an MCL pie-crusting technique. Although Mostafa Zaky Abdelrazek et al 8 introduced a technique to repair ramp lesions using standard anterior portals, they visualized the posteromedial compartment by positioning the arthroscope through the intercondylar notch, which requires a high level of surgical skill.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…4,9,15 However, to our knowledge, no techniques have been reported that enable full visualization of the ramp lesion directly from the anterior compartment using an arthroscope placed through the anterolateral portal (without posteromedial visualization through the intercondylar notch) and repair of the lesion from the anteromedial portal using an MCL pie-crusting technique. Although Mostafa Zaky Abdelrazek et al 8 introduced a technique to repair ramp lesions using standard anterior portals, they visualized the posteromedial compartment by positioning the arthroscope through the intercondylar notch, which requires a high level of surgical skill.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike previous reports that introduced MCL release as a technique only for patients with a tight medial compartment, we use this technique in all cases; it allows direct anterior visualization of the posteromedial part of the medial meniscus from the anterolateral portal. 8 Many previous studies have established that MCL release is a safe and minimally harmful technique. [16][17][18][19] MCL pie crusting has typically generated grade I MCL laxity without saphenous nerve or vein By means of medial collateral ligament release, the ramp lesion, which is usually covered by the medial femoral condyle, can be seen from the standard anterolateral viewing portal.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations